Never Change: The History and Aesthetics that Inspired Still Country - Mackwell, Alan. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Music.; Advisor: John McDonald.; Committee: Joseph Auner, and Kareem Roustom.; Keyword: Music.